Cabo Verde: dilemas étnico-identitários num território fluido - Cláudio Alves Furtado (Universidade do Vale do Rio dos Sinos (UNISINOS), 2013)
Cape Verdean identity has been the subject of questions, doubts and quarrels. Its archipelagic condition its type of settlement and the workings of its colonization are not entirely unrelated to its identity. It could be said that they are structural to the ambiguities, ambivalences and contradictions which pervade the multiple narratives (re)produced, appropriated and re-appropriated in the most disparate moments in Cape Verde's history, as well as to the practices that embody social interactions among Cape Verdeans and between themselves and others, particularly Europeans and continental Africans. A profusion of essays, theses and books has been recently produced to deal with the matter of identity. In our judgment, that reiterates an ambiguity - whose existential dimension cannot be neglected - that encompasses it. Moreover, such a profusion tends to demonstrate the complexity of the issue rather than its depletion. This paper does not intend to exhaust the debate on this matter. Rather, it proposes a discussion about the ways Cape Verdean society - intellectual and political elites as much as the ordinary citizen - has coped with the process of identity construction as a crossroads, both spatial and symbolic.